CONSTITUTIONALITY OF THE NOKEN SYSTEM IN THE CENTRAL PAPUA REGIONAL ELECTIONS BASED ON THE PANCASILA DEMOCRACY STATE - Marsudi, Kenlies Era Rosalina; Galih Kurniawan, Bekti; Nuraini, Siti (JURNAL SETIA PANCASILA, 2025)
This study explores the constitutionality of the noken voting system in the 2024 Papua Tengah gubernatorial election from the perspective of the Pancasila democratic state. This election marks a historic milestone as the first gubernatorial election since the establishment of Papua Tengah Province in 2022. The central issue lies in the tension between procedural democratic principles and noken as a form of communal democracy based on consensus. This research addresses a gap in multidisciplinary literature examining noken from the perspectives of legal-political legitimacy, democratic systems, and national constitutional law. Using a qualitative approach, data were collected through in-depth interviews, non-participatory observation, and document analysis, then analyzed thematically. The findings reveal that the noken system is constitutionally grounded, referring to Pasal 18B ayat (2) UUD 1945, aligned with the fourth principle of Pancasila democracy emphasizing deliberation, and consistent with legal pluralism theory that recognizes customary law within a national legal framework. Furthermore, the system is compatible with Papua’s special autonomy as stipulated in Undang-Undang Nomor 2 Tahun 2021. However, field implementation presents significant challenges, particularly the risk of abuse by local political elites, dominance of tribal leaders, lack of direct public participation, and the absence of clear technical regulations and effective oversight mechanisms. While some respondents view noken as contradictory to the principles of direct, general, free, confidential, honest, and fair elections, others consider it a legitimate form of communal democracy unique to Papua, provided there is strong regulation and oversight. The study concludes that the noken system remains relevant within the framework of Papua's special autonomy, but regulatory reforms and supervisory mechanisms are essential to ensure alignment with the dynamic and contextual principles of Pancasila democracy.